An information system on the three major components of elementary science teaching - Soriano, Amor Torres
The study is concerned with evolving an information system concerning 3 major components of science teaching, namely, teacher qualification, classroom interaction and physical facilities based on data from 20 percent of the science teachers in 10 selected Central and Barrio Schools in Laguna. The Flanders' system of interaction analysis was used to analyze the classroom instructional procedures in 52 science classroom sessions which were observed, tape recorded, coded, and plotted in matrix. The science teachers differ widely in educational attainment with the central school teachers having slightly better academic preparation than the barrio school teachers. In both the central and barrio schools, the BSEE and the ETC-BSE graduates performed better than the BSE graduates in the tests on knowledge of subject matter. Science classes are teacher-dominated with the central school classes more teacher-dominated than the barrio classes.